Deciphering the Oncogenic Role of VPS28 Modulated by miR-491-5p in Breast Cancer Cells Using In Silico and Functional Analysis - Shi, Wenjie; Hu, Daojun; Xing, Yu; Zhuo, Rui; Lao, Qiufeng; Liu, Hui; Pang, Weiyi (Frontiers in Molecular Biosciences, 2021)
Vacuolar protein sorting-associated protein 28 (VPS28), one of four cytosolic proteins comprising the endosomal sorting complex required for transport I (ESCRT-I) component, has been reported to be linked to various cancers. However, less evidence is available regarding the involvement of VPS28 in breast cancer. To this end, this study focused on exploring the function of VPS28 in breast cancer cells using in silico analysis. VPS28 expression pattern data in breast cancer tissues was collected using TCGA and CPTAC databases and analyzed to assess the association of VPS28 with breast cancer prognosis. Elevated VPS28 expression was found in breast cancer tissues and was associated with a poor prognosis (P < 0.001). Higher VPS28 expression indicated a short survival duration (HR = 2.43; 95% CI: 1.44 - 4.1; P < 0.001). The CCLE database showed that VPS28 was expressed in breast cancer cell lines. The upstream targets of VPS28 were identified using the mirDIP, starBase, and TargetScan online tools. The correlation and binding relationship between miR-491-5p and VPS28 were analyzed. VPS28 or miR-491-5p gain and loss of function experiments were performed to verify their potential effect on the biological functions of breast cancer cells. Knockdown of VPS28 was shown to suppress the biological functions and enhance the apoptosis of breast cancer cell lines. Micro RNA-491-5p, identified as a post-transcriptional regulator of VPS28, was downregulated in breast cancer tissues. In contrast to the miR-491-5p inhibitor, the miR-491-5p mimic could suppress the migration, wound healing ability, and proliferation of, while accelerating apoptosis. However, co-transfection of VPS28 and miR-491-5p counteracted the effect of the miR-491-5p mimic on breast cancer cell functions. Thus, our in silico analysis demonstrates that miR-491-5p can suppress breast cancer progression by attenuating the expression of VPS28.